Thermal degradation kinetics of polyesters containing mesogenic aromatic diols - Mule, Smita Atmaram; Ghadage, R. S.; Jacob, Nalini E.; Rajan, C. R.; Ponrathnam, Surendra (Journal Applied Polymer Science, 2005)
A series of polyesters were synthesized by reacting structurally differing aromatic diols with either saturated (flexible) or unsaturated (rigid) dicarboxylic acid halide by a stirred interfacial polycondensation technique. Thermal degradation kinetics of these polyesters were investigated by applying Coats-Redfern and Horowitz-Metzger nonisothermal procedures. The dynamic thermogravimetry experiments were conducted in nitrogen to obtain differential thermogravimetric plots. Thermal stability of these polyesters was discussed on the basis of semiquantitative methods such as differential procedural decomposition temperature, integral procedural decomposition temperature, and fraction decomposition temperature (e.g., 10 % DT). Degradation proceeded in multiple stages. The thermal degradation patterns and activation energies in these stages were discussed in relation to central bridging moieties of aromatic diol. The activation energies of these polyesters were found to be in the range of 100 to 200 kJ/mol. The effect of spacer type on activation energy was also reported. (c) 2005 Wiley Periodicals, Inc.
Keywords: Activation energy; Degradation; kinetics (polym.); Polycondensation; polyesters

Molecular dynamics of copolyester/clay nanocomposites as investigated by viscoelastic and dielectric analysis - Kalgaonkar, Rajendra A.; Jog, Jyoti Prakash (Journal of Polymer Science Part B-Polymer Physics, 2008)
We have investigated the molecular dynamics of poly(ethylene glycol-co-cycloxeane-1,4-dimethanol terephthalate) (PETG) nanocomposites based on a organically modified layered silicate. Intercalated namocomposites were prepared by melt compounding technique as evidenced from the X-ray diffraction and transmission electron microscopy studies. Two relaxation processes were observed in pure PETG as well as in the nanocomposites. The low-temperature beta-process was assigned to the local motions of C=O polar groups and the alpha-process was due to the glass-rubber transition or the segmental relaxations associated with the polymer chain backbone. Presence of layered silicates accelerated alpha-relaxation dynamics in the nanocomposites accompanied by a depression in T(g) which was attributed to the reduced intermolecular cooperativity between intercalated polymers chains. Additionally, a direct comparison between the viscoelastic and dielectric studies shows excellent agreement between the accelerated alpha dynamics of the nanocomposites. (C) 2008 Wiley Periodicals, Inc. J Polym Sci Part B: Polym Phys 46: 2539-2555, 2008
Keywords: clay; Dielectric relaxation; Nanocomposites; polyesters

Synthesis and characterization of polyesters based on 1,1,1-[bis(4-hydroxyphenyl)-4 `-pentadecylphenyl]ethane - More, Arvind S.; Naik, Parimal V.; Kumbhar, Kishor P.; Wadgaonkar, Prakash P. (Polymer International, 2010)
Aromatic polyesters are of considerable interest because of their excellent mechanical properties, chemical resistance and thermal stability. However, most aromatic polyesters are difficult to process due to their high glass transition temperatures coupled with their insolubility in common organic solvents. The present article describes a series of organosoluble polyesters and copolyesters based on 1,1,1-[bis(4-hydroxyphenyl)-4'-pentadecylphenyl]ethane. A series of new aromatic polyesters containing pendant pentadecyl chains was synthesized by interfacial polycondensation of 1,1,1-[bis(4-hydroxyphenyl)-4'-pentadecylphenyl]ethane with terephthalic acid chloride (TPC), isophthalic acid chloride (IPC) and a mixture of TPC and IPC. A series of copolyesters was synthesized from 4,4'-isopropylidenediphenol with TPC by incorporating 1,1,1-[bis(4-hydroxyphenyl)-4'-pentadecylphenyl]ethane as a comonomer. Inherent viscosities of the polyesters and copolyesters were in the range 0.72-1.65 dL g(-1) and number-average molecular weights were in the range 18 170-87 220. The polyesters and copolyesters containing pendant pentadecyl chains dissolved readily in organic solvents such as chloroform, dichloromethane, pyridine and m-cresol and could be cast into transparent, flexible and apparently tough films. Wide-angle X-ray diffraction data revealed the amorphous nature of the polyesters and copolyesters. The formation of loosely developed layered structure was observed due to the packing of pendant pentadecyl chains. The temperature at 10% weight loss, determined using thermogravimetric analysis in nitrogen atmosphere, of the polyesters and copolyesters containing pendant pentadecyl chains was in the range 400-460 degrees C. The polyesters and copolyesters exhibited glass transition temperatures in the range 63-82 degrees C and 177-183 degrees C, respectively. (C) 2010 Society of Chemical Industry
Keywords: cashew nutshell liquid; CNSL; pentadecyl; polyesters; renewable

Design and synthesis of aromatic polyesters bearing pendant clickable maleimide groups - Nagane, Samadhan S.; Kuhire, Sachin S.; Jadhav, Uday A.; Dhanmane, Sushilkumar A.; Wadgaonkar, Prakash P. (Journal of Polymer Science Part A-Polymer Chemistry, 2019)
A bisphenol bearing pendant maleimide group, namely, N-maleimidoethyl-3, 3-bis(4-hydroxyphenyl)-1-isobenzopyrrolidone (PPH-MA) was synthesized starting from phenolphthalein. Aromatic (co)polyesters bearing pendant maleimide groups were synthesized from PPH-MA and aromatic diacid chlorides, namely, isophthaloyl chloride (IPC), terephthaloyl chloride (TPC), and 50:50 mol % mixture of IPC and TPC by low temperature solution polycondensation technique. Copolyesters were also synthesized by polycondensation of different molar proportions of PPH-MA and bisphenol A with IPC. Inherent viscosities and number-average molecular weights of aromatic (co)polyesters were in the range of 0.52-0.97 dL/g and 20,200-32,800 g/mol, respectively indicating formation of medium to reasonably high-molecular-weight polymers. C-13 NMR spectral analysis of copolyesters revealed the formation of random copolymers. The 10% weight loss temperature of (co)polyesters was found in the range 470-484 degrees C, indicating their good thermal stability. A selected aromatic polyester bearing pendant maleimide groups was chemically modified via thiol-maleimide Michael addition reaction with two representative thiol compounds, namely, 4-chlorothiophenol and 1-adamantanethiol to yield post-modified polymers in a quantitative manner. Additionally, it was demonstrated that polyester containing pendant maleimide groups could be used to form insoluble crosslinked gel in the presence of a multifunctional thiol crosslinker. (c) 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2019, 57, 630-640
Keywords: crosslinking; maleimide group; modification; polyesters; thiol-maleimide

Thermally crosslinkable and chemically modifiable aromatic polyesters possessing pendant propargyloxy groups - Verma, Savita; Maher, Deepak M.; Nagane, Samadhan S.; Tawade, Bhausaheb V.; Wadgaonkar, Prakash P. (Journal of Polymer Science Part A-Polymer Chemistry, 2019)
New aromatic (co)polyesters containing pendant propargyloxy groups were synthesized by phase transfer-catalyzed interfacial polycondensation of 5-(propargyloxy)isophthaloyl chloride (P-IPC) and various compositions of P-IPC and isophthaloyl chloride with bisphenol A. FTIR and NMR spectroscopic data, respectively, revealed successful incorporation of pendant propargyloxy groups into (co)polyesters and formation of (co)polyesters with desired compositions. (Co)polyesters exhibited good solubility in common organic solvents such as chloroform, dichloromethane, and tetrahydrofuran and could be cast into transparent, flexible, and tough films from chloroform solution. Inherent viscosities and number average molecular weights of (co)polyesters were in the range 0.77-1.33 dL/g and 43,600-118,000 g/mol, respectively, indicating the achievement of reasonably high-molecular weights. The 10% weight loss temperatures of (co)polyesters were in the range 390-420 degrees C, demonstrating their good thermal stability. (Co)polyesters exhibited T-g in the range 146-170 degrees C and T-g values decreased with increase in mol % incorporation of P-IPC. The study of non-isothermal curing by DSC indicated thermal crosslinking of (co)polyesters via propargyloxy groups. The utility of pendant propargyloxy group was demonstrated by post-modification of the selected copolyester with 1-(4-azidobutyl)pyrene, 9-(azidomethyl)anthracene, and azido-terminated poly(ethyleneglycol) monomethyl ether via copper(I)-catalyzed Huisgen 1,3-dipolar cycloaddition reaction. FTIR and H-1 NMR spectra confirmed that click reaction was quantitative. (c) 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2019, 57, 588-597
Keywords: Click chemistry; crosslinking; modification; polyesters; propargyloxy; step-growth polymerization

Manipulating hydrophobicity of polyester nanofiber mats with egg albumin to enhance cell interactions - Patel, Pratikshkumar R.; Pandey, Komal; Killi, Naresh; Gundloori, Rathna Venkata Naga (Polymer Engineering and Science, 2021)
A hybrid of poly-l-lactic acid (PLA) and poly-epsilon-caprolactone (PCL) system was designed using hydrophilic generally regarded as safe (GRAS) protein, egg albumin (EA), and fabricated as nanofiber mats (NM) to facilitate improved cell interactions and functionality. Our studies include, preparation and analysis of physicochemical properties of NM. Surface morphology of NM was smooth with the diameter ranging from 250 to 400 nm. The contact angle of NM decreased from 80 to 45 degrees with the increase in EA concentration. The rate and extent of swelling was increased 3-folds with the addition of EA. Release studies of NM showed maximum amount of MTz was released with the increase in MTz concentration (>85%). The MTz interaction with EA and structure stability of EA was confirmed from fluorescence and circular dichroism studies. NM showed increase in inhibition of bacterial growth of Staphylococcus aureus and Escherichia coli with the increase in MTz concentration. Cell viability of the NM was >80% and also, the cell proliferation increased as EA content increased. NM hemolytic activity was less than 5% suggesting compatibility. Hence, results concluded that EA had regulated hydrophobicity, promoted cell interactions, and proliferation and therefore, NM is considered safe for tissue regeneration.
Keywords: Biocompatibility; Biomaterials; drug delivery systems; egg albumin; electrospinning; nanofibers; polyesters